Physical Exercise Training versus Relaxation in Allogeneic stem cell transplantation (PETRA study): rationale and design of a randomized trial to evaluate a yearlong exercise intervention on overall survival and side-effects after allogeneic stem cell transplantation - Wiskemann, Joachim; Kühl, Rea; Dreger, Peter; Huber, Gerhard; Kleindienst, Nikolaus; Ulrich, Cornelia; Bohus, Martin (BMC cancer, 2015)
Background: Allogeneic stem cell transplantation (allo-HCT) is associated with high treatment-related mortality and innumerable physical and psychosocial complications and side-effects, such as high fatigue levels, loss of physical performance, infections, graft-versus-host disease (GvHD) and distress. This leads to a reduced quality of life, not only during and after transplantation, but also in the long term. Exercise interventions have been shown to be beneficial in allo-HCT patients. However, to date, no study has focused on long-term effects and survival. Previous exercise studies used ‘usual care’ control groups, leaving it unclear to what extent the observed effects are based on the physical effects of exercise itself, or rather on psychosocial factors such as personal attention. Furthermore, effects of exercise on and severity of GvHD have not been examined so far. We therefore aim to investigate the effects and biological mechanisms of exercise on side-effects, complications and survival in allo-HCT patients during and after transplantation. Methods/design: The PETRA study is a randomized, controlled intervention trial investigating the effects of a yearlong partly supervised mixed exercise intervention (endurance and resistance exercises, 3–5 times per week) in 256 patients during and after allogeneic stem cell transplantation. Patients in the control group perform progressive muscle relaxation training (Jacobsen method) with the same frequency. Main inclusion criterion is planned allo-HCT. Main exclusion criteria are increased fracture risk, no walking capability or severe cardiorespiratory problems. Primary endpoint is overall survival after two years; secondary endpoints are non-relapse mortality, median survival, patient reported outcomes including cancer related fatigue and quality of life, physical performance, body composition, haematological/immunological reconstitution, inflammatory parameters, severity of complications and side-effects (e.g. GvHD and infections), and cognitive capacity. Discussion: The PETRA study will contribute to a better understanding of the physiological and psychological effects of exercise training and their biological mechanisms in cancer patients after allo-HCT. The ultimate goal is the implementation of optimized intervention programs to reduce side-effects and improve quality of life and potentially prognosis after allogeneic stem cell transplantation.